Eye Movements Interfere With Limb Motor Control in Stroke Survivors. (August 2018) - Singh, Tarkeshwar; Perry, Christopher M.; Fritz, Stacy L.; Fridriksson, Julius; Herter, Troy M.
Background . Humans use voluntary eye movements to actively gather visual information during many activities of daily living, such as driving, walking, and preparing meals. Most stroke survivors have difficulties performing these functional motor tasks, and we recently demonstrated that stroke survivors who require many saccades (rapid eye movements) to plan reaching movements exhibit poor motor performance. However, the nature of this relationship remains unclear. Objective . Here we investigate if saccades interfere with speed and smoothness of reaching movements in stroke survivors, and if excessive saccades are associated with difficulties performing functional tasks. Methods . We used a robotic device and eye tracking to examine reaching and saccades in stroke survivors and age-matched controls who performed the Trail Making Test, a visuomotor task that uses organized patterns of saccades to plan reaching movements. We also used the Stroke Impact Scale to examine difficulties performing functional tasks. Results . Compared with controls, stroke survivors made many saccades during ongoing reaching movements, and most of these saccades closely preceded transient decreases in reaching speed. We also found that the number of saccades that stroke survivors made during ongoing reaching movements was strongly associated with slower reaching speed, decreased reaching smoothness, and greater difficulty performing functional tasks. Conclusions . Our findings indicate that poststroke interference between eye and limb movements may contribute to difficulties performing functional tasks. This suggests that interventions aimed at treating impaired organization of eye movements may improve functional recovery after stroke.